Nutritional characterization and antioxidant properties of various edible portions of Cucurbita maxima: A potential source of nutraceuticals - Farhana Jahan; Md. Badrul Islam; Shyama Prosad Moulick; Mahci Al Bashera; Md. Sabbir Hasan; Nishat Tasnim; Trissa Saha; Farhana Boby; Md. Waliullah; Anik Kumar Saha; Amin Hossain; Lailatul Ferdousi; et al. (Heliyon, 2023)
Pumpkin (Cucurbita maxima) is a widely grown vegetable in Bangladesh and is known as the sole supplier of various nutrients. Many studies evidence the nutritional value of flesh and seed while peel, flower, and leaves were reported scarcely with limited information. Therefore, the study aimed to investigate the nutritional composition and antioxidant properties of flesh, peel, seed, leaves, and flowers of Cucurbita maxima. The seed had a remarkable composition of nutrients and amino acids. Flowers and leaves possessed higher content of minerals, phenols, flavonoids, carotenes, and total antioxidant activity. The order of IC50 value (peel > seed > leaves > flesh > flower) indicates higher DPPH radicals scavenging activity of the flower. Moreover, a significant positive relationship was observed among these phytochemical constituents (TPC, TFC, TCC, TAA) and DPPH radicals scavenging activity. It could be concluded that these five parts of the pumpkin plant have an intense potency to be an exigent component of functional food or medicinal herbs.